“Los roles del docente y estudiantes en la educación virtual en tiempos de pandemia.” - Lagua Caiza, Johana Maricela (2021)
Virtual education requires new educational roles, which comply with responsibility and commitment to the knowledge imparted through the management of different technological tools. Currently education took an unexpected turn due to the Covid-19 health crisis. In which, the educational community had to abide by the new teaching modality, through the use of social networks or virtual platforms; in addition to dealing with the use of tangible and intangible technological resources. Recognizing the roles of teachers and students in virtual education due to the health crisis of covid-19 at “Dr. Trajano Naranjo Iturralde”, Elementary School -2020, the qualitative approach was used as a research methodology, which describes the characteristics and qualities of the main authors of education. The interview, as an instrument, and a guide technique, were used which allowed to collect the necessary data for the investigative process. As a result, the transfer of knowledge about the use of the Google Meet tool is obtained, through the development of an educational web page. In addition, this research importance is the recognition of the new pedagogical roles carried out in ICT. Likewise, the contribution is obtained with the teachers’ reflection who put aside the traditional paradigm, for the didactic material- digital creation, the same that strengthens and relates previous knowledge with new significant learning.